Creating a Value Proposition for Geriatric Care : The Transformation of American Healthcare - Powers, James S. (Springer International Publishing : Imprint: Springer, 2017)
This book creates a value proposition in geriatric care - a promise of value to be delivered to improve care and to provide specific benefits to healthcare systems. It describes strategies and understanding of the incentives, barriers encountered in promoting changes in the healthcare systems, and discusses numerous examples and outcomes. Drawn from many fields such as medicine and science, sociology, politics, business and economics, the book helps guide the introduction of geriatric principles into mainstream medical care with the goal of improving the care and quality of life of older persons in all healthcare systems.
Keywords: Medicine.; Health care management.; Health services administration.; Geriatric nursing.; elektronické knihy; electronic books